2020
DOI: 10.1038/s41598-020-59003-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of palladated porous nitrogen-doped carbon using halloysite as porogen: disclosing its utility as a hydrogenation catalyst

Abstract: in this article, halloysite nanoclay (Hal) was used as porogen for the synthesis of nitrogen doped porous carbon material with high specific surface area and pore volume. To this purpose, polymerization of melamine and terephthalaldehyde (Mt) was performed in the presence of amine-functionalized carbon coated Hal (Hal@Glu-2N) that was prepared from hydrothermal treatment of Hal and glucose. Then, the prepared nanocomposite was palladated and carbonized to afford Pd@Hal@C. To further improve the textural proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…introduced Pd@C (Figure 26) as an efficient catalyst for the hydrogenation of nitroarenes in aqueous media (Scheme 60). [111] The procedure used for the preparation of catalyst involved several steps: hydrothermal treatment of halloysite and glucose, functionalization with the amine, polymerization of melamine and terephthalaldehyde (MT), incorporation of Pd, calcination, and finally washing with HF to increase the specific surface area and introduce more pores in the structure of the nanocomposite. The authors also compared the catalytic activity of Pd@C with that of Pd@Hal, Pd@Hal@Glu, Pd@Hal@C and Pd@Hal@Glu‐MT in the hydrogenation of nitrobenzene (Scheme 38), and the activity of Pd@C was superior due to the increased interactions of the N atoms of the support with Pd, enhanced Pd loading as well as improved mass transport.…”
Section: Heteroatom‐doped Porous Carbon/metal Catalystsmentioning
confidence: 99%
“…introduced Pd@C (Figure 26) as an efficient catalyst for the hydrogenation of nitroarenes in aqueous media (Scheme 60). [111] The procedure used for the preparation of catalyst involved several steps: hydrothermal treatment of halloysite and glucose, functionalization with the amine, polymerization of melamine and terephthalaldehyde (MT), incorporation of Pd, calcination, and finally washing with HF to increase the specific surface area and introduce more pores in the structure of the nanocomposite. The authors also compared the catalytic activity of Pd@C with that of Pd@Hal, Pd@Hal@Glu, Pd@Hal@C and Pd@Hal@Glu‐MT in the hydrogenation of nitrobenzene (Scheme 38), and the activity of Pd@C was superior due to the increased interactions of the N atoms of the support with Pd, enhanced Pd loading as well as improved mass transport.…”
Section: Heteroatom‐doped Porous Carbon/metal Catalystsmentioning
confidence: 99%
“…Based on previous literature 33 with little modi cation, to immobilize Palladium NPs on the h-Fe 2 O 3 @glu-MFR, a solution of Pd(OAc) 2 (2 wt.%) in MeOH (10 mL) was added to the solution of suspended h-Fe 2 O 3 @glu-MFR (1 g) in toluene (50 mL) in a drop wise manner under stirring condition overnight. In the following, a solution of NaBH 4 in MeOH (12 mL, 0.1 N) was added under inert atmosphere to the abovementioned suspension.…”
Section: Immobilization Of Palladium Nps On H-fe 2 O 3 @Glu-mfr (E)mentioning
confidence: 99%
“…The resulting Pd@h-Fe 2 O 3 @C was prepared by previous method 33 . To this propose, Pd@h-Fe 2 O 3 @glu-MFR (5 g) was placed in a quartz container and heated up to 450 °C for 1 h under argon ow and heating rate of 30 °C min -1 .…”
Section: Synthesis Of Pd@h-fe 2 O 3 @C (F)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the continuation of our research on disclosing the catalytic utility of Hal 23,24 , recently we have reported facile recovery and high reusability of magnetic Hal 25,26 . On the other hand, our research on the catalytic activity of IL-Hal hybrid 27,28 showed that the presence of ILs on the Hal can efficiently improve anchoring of nanoparticles and suppressing their leaching.…”
mentioning
confidence: 94%